Environmental Education: a tool to promote wild birds’ welfare (Biocenosis, 2021)
Abstract: This article exposes pressing environmental issues affecting wild birds. Such issues are many times caused by the actions of people who are not environmentally educated. Likewise, in their eagerness to help, but because of lack of knowledge, some individuals make serious mistakes regarding the correct way of treating wild birds. Therefore, this article provides some recommendations to promote well-being and proper management of wild birds. Moreover, in order to work on the subject and raise awareness, simple, practical, and low-cost environmental education techniques are offered. Finally, a list of the environmental teaching resources available in the country is also provided.